When God stops fighting: how religious violence ends - Juergensmeyer, Mark (University of California Press, 2022)
A gripping study of how religiously motivated violence and militant movements end, from the perspectives of those most deeply involved. How does religious violence end? When God Stops Fighting probes for answers through case studies and personal interviews with militants associated with the Islamic State (ISIS) in Iraq, the Sikh Khalistan movement in India's Punjab, and the Moro movement for a Muslim Mindanao in the Philippines. Mark Juergensmeyer is arguably the globe's leading expert on religious violence, and for decades his books have helped us understand the worlds and worldviews of those who take up arms in the name of their faith. But even the most violent of movements, consumed by grand religious visions of holy warfare, eventually come to an end. In order to understand what led to these drastic changes in the attitudes of men and women once devoted to all-out ideological war, Juergensmeyer takes readers on an intimate journey into the minds of religiously motivated militants. Readers will travel with Juergensmeyer to the affected regions, examine compelling stories of devotion and reflection, and meet with people related to the movements and impacted by them to understand how their worldviews can, and do, change. Building on the author's lifetime of fieldwork interviewing religious combatants around the world, When God Stops Fighting reveals how the transformation of religious violence appears to those who once promoted it as the only answer.